Studi Erosi Menggunakan Model Agricultural Non-Point Source Pollution (AGNPS) pada DAS Kali Lamong Provinsi Jawa Timur - Majid, Haidar Naufal; Sholichin, Moh.; Asmaranto, Runi (Jurusan Teknik Pengairan, Fakultas Teknik, Universitas Brawijaya, 2020)
Perubahan tata guna lahan dari yang semula hutan menjadi lahan pertanian, perkebunan, maupun ladang berdampak pada tingginya laju erosi pada DAS Kali Lamong, Kabupaten Gresik, Provinsi Jawa Timur. Studi ini bertujuan untuk memetakan kondisi existing persebaran laju erosi beserta tingkat bahaya erosi pada DAS Kali Lamong, sehingga kemudian dapat diberikan saran penanggulangan berupa skenario lahan baru. Perhitungan menggunakan model Agricultural Non-Point Source Pollution (AGNPS) diperoleh laju erosi rata-rata DAS sebesar 31,771 ton/ha/tahun. Hasil analisis tingkat bahaya erosi berdasarkan Indeks Bahaya Erosi oleh Hammer (1981) diperoleh indeks dengan tingkat rendah (indeks <1) seluas 460,8 km2, tingkat sedang (indeks 1-4) seluas 200,88 km2, tingkat tinggi (indeks 4-10) seluas 42,93 km2, dan tingkat sangat tinggi (indeks >10) seluas 63,27 km2. Berdasarkan perhitungan sediment delivery ratio (SDR), didapatkan hasil perkiraan sedimen sebesar 34.228,031 ton/tahun atau 28.532,231 m3/tahun. Skenario lahan baru disusun berdasarkan RLKT - Departemen Kehutanan. Dari hasil simulasi skenario lahan baru, tidak didapati indeks bahaya erosi pada tingkat tinggi maupun sangat tinggi. Hasil tersebut menunjukkan skenario lahan yang baru dapat mengurangi laju erosi dan tingkat bahaya erosi pada DAS Kali Lamong. The transformation of land-use from forestry into agricultures, plantations, and fields have an impact on the high-rate of erosion at Kali Lamong Watershed, Gresik Regency, East Java Province. This study is purposed to map the existing condition of the erosion rate and the erosion hazard level at Kali Lamong Watershed, so that it can be resolved in the form of a new land-use scenario recommendation. Based on the calculation by using the Agricultural Non-Point Source Pollution (AGNPS) model, it is obtained the watershed’s average erosion rate of 31,771 ton/ha/year. The analysis result of the erosion hazard level using the Erosion Hazard Index by Hammer (1981), shows that the index at low level (index <1) in an area of 460,8 km2, medium level (index 1-4) in an area of 200,88 km2, high level (index 4-10) in an area of 42,93 km2, and very high level (index >10) in an area of 63,27 km2. Based on the calculation of the sediment delivery ratio (SDR), it is obtained the sediment value of 34.228,031 ton/year or 28.532,231 m3/year. The new land-use scenario is arranged based on RLKT from the Indonesian Department of Forestry. From the simulation of the new land-use scenario result, it is not obtained the erosion hazard index at either high or very high level. The result shows that the new land-use scenario can reduce the erosion rate and the erosion hazard level at Kali Lamong Watershed.